The Effect of Good Corporate Governance, Earning Management on Firm Value - Wahyu Fikri Darmawan; Umaimah Umaimah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Firm value serves as a long-term goal to attract investors and ensure sustainable growth, while Good Corporate Governance (GCG) addresses agency conflicts to enhance value. Specific Background: Enterprise value and GCG are essential for creating ethical, competitive, and resilient organizations, enabling firms to navigate global economic and social challenges. Knowledge Gap: Despite prior research, inconsistencies remain regarding the impact of GCG and earnings management on firm value, necessitating further study. Aims: This study examines the influence of GCG, earnings management, and firm-specific factors on firm value, providing insights for investment decisions. PBV is used as a proxy for firm value, while the Jones model represents earnings management, with GCG measured through board composition, independent commissioners, and audit committees. Methods: Using a quantitative approach, the study analyzed 155 data points from new coal mining companies listed on the Indonesia Stock Exchange (2019–2023) through purposive sampling and documentation techniques. Results: The board of directors significantly enhances firm value, while the audit committee and independent commissioners are less effective. Earnings management negatively impacts firm value by creating informational asymmetry. Novelty: By integrating signal theory, the study offers a unique perspective on mitigating information asymmetry through transparent reporting. Implications: The findings contribute to improving corporate governance practices and guiding investment strategies.